SANKSI PIDANA SEBAGAI UPAYA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA ILLEGAL FISHING - Deni Juliyanto; Zainab Ompu Jainah (JOURNAL OF LAW AND NATION, 2026)
The very concerning level of deviation in fishing efforts is often found by both individuals and corporations that are carried out illegally or against the law. This study aims to determine the criminal sanctions and law enforcement against the crime of illegal or against the law fishing. Through secondary data analysis and interviews with law enforcement officers, this study found that the criminal sanctions for the crime of illegal fishing based on the Fisheries Law can be subject to a prison sentence of 10 years and a fine of IDR. 2,000,000,000 (Two Billion Rupiah). A qualitative approach is used to identify the stages of criminal law enforcement that influence the success of the law enforcement process against the crime of illegal or against the law fishing.